Citizen Relationship Management (CnRM) to Build the Awareness of Anti-Corruption: Collaborative Governance Perspective - Sukarno, Gendut; Azizah, Nurul; Nawangsari, Ertien Rining; Izaak, Wilma Cordelia; Farida, Siti Ning (International Journal of Psychosocial Rehabilitation, 2020)
KPK is an independent institution that has a special obligation in eradicating corruption in Indonesia, but in carrying out its duties many obstacles and threats that so far have not yet found a solution. Seeing the demographic bonus that is currently being experienced by Indonesia, it is thought that intermittent between 2020-2035 is an opportunity as well as a threat that must be addressed wisely. Citizen Relationship Management (CnRM) is a new concept in managing internet-based national resources relating that the internet waves are undeniable. So that in the future practice of CnRM through collaborative governance is able to bring the future of the Indonesian people to be better. Using a qualitative approach from a variety of literature brings up a concept oriented to practical thinking. CnRM is an effort to instill a love for the nation wherever the citizens of a country are located, which means it has strong boundary to the nation. More specifically CnRM in this article focuses on moral issues for anti-corruption awareness. Based on a variety of literature and collaborations from the fields of science, the concept of thinking related to CnRM is obtained and how the flow of implementation in practice in the future. The implementation of CnRM as an effort to raise awareness of anti- corruption through collaborative governance is expected to be a media in the direction of a corruption-free gold generation in Indonesia.